2021
DOI: 10.3390/molecules26226892
|View full text |Cite
|
Sign up to set email alerts
|

HPTLC and FTIR Fingerprinting of Olive Leaves Extracts and ATR-FTIR Characterisation of Major Flavonoids and Polyphenolics

Abstract: The aim of this study was to analyse the effect of spontaneous microbial maceration on the release and extraction of the flavonoids and phenolics from olive leaves. Bioprofiling based on thin-layer chromatography effect-directed detection followed by ATR-FTIR spectroscopy proved to be a reliable and convenient method for simultaneous comparison of the extracts. Results show that fermentation significantly enhances the extraction of phenolic compounds and flavonoids. The polyphenolic content was increased from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 48 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…As can be seen from Figure 2 (FSL-1), the broad and strong absorption peaks at 3,385 cm −1 wave number indicate the presence of a large number of phenolic hydroxyl groups; the characteristic absorption peaks at 2,917 cm −1 , 2,853 cm −1 , 1,380 cm −1 are –CH3, –CH2, indicating the presence of hydrogen on saturated carbon; the characteristic peaks at 1,630, 1,610, 1,540, and 1,450 cm −1 are benzene ring peaks. The absorption peaks at 1670 cm −1 are C = 0 stretching vibration peaks, in which the group may be conjugated with the hydroxyl group causing its absorption peak to move to lower wave number, and at 1,260 and 1,090 cm −1 can be attributed to the antisymmetric and symmetric stretching vibration peaks of the ether bond, Analysis results indicate that the extract is a flavonoid ( Agatonovic-Kustrin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 93%
“…As can be seen from Figure 2 (FSL-1), the broad and strong absorption peaks at 3,385 cm −1 wave number indicate the presence of a large number of phenolic hydroxyl groups; the characteristic absorption peaks at 2,917 cm −1 , 2,853 cm −1 , 1,380 cm −1 are –CH3, –CH2, indicating the presence of hydrogen on saturated carbon; the characteristic peaks at 1,630, 1,610, 1,540, and 1,450 cm −1 are benzene ring peaks. The absorption peaks at 1670 cm −1 are C = 0 stretching vibration peaks, in which the group may be conjugated with the hydroxyl group causing its absorption peak to move to lower wave number, and at 1,260 and 1,090 cm −1 can be attributed to the antisymmetric and symmetric stretching vibration peaks of the ether bond, Analysis results indicate that the extract is a flavonoid ( Agatonovic-Kustrin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 93%
“…In their research, Abaza et al, 17 observed the highest recovery of avonoids from olive leaves extracted using 50% acetone through an ultrasound-assisted system for 10 min at 60 °C. Agatonovic-Kustrin et al, 18 described the effectiveness of fermentation extraction with lactic acidforming bacteria using ethyl acetate in the improved yield of avonoids that reached up to 238 mg rutin equivalents/20 mL of olive leaf extract. Also, in the study of Lins et al, 19 the commercial micronized dry olive leaf powders (superneground) when extracted with 80% methanol produced 19.4 mg quercetin equivalents per g olive leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Another inuential factor in the recovery of verbascoside from olive leaves evidently is the processing approach. Particular examples of the values reported in previous studies are: 18.5 mg g −1 using ultrasound-assisted extraction; 22.9 ppm using cloud point extraction based on the salting-out phenomenon; 3.90 mg g −1 in Picual leaf extracts using microwave extraction with water. [46][47][48] Flavonoid derivatives.…”
Section: Recovery Of Principal Polar Phenols From Olive Leaveschromat...mentioning
confidence: 97%
“…The weak bands observed in the range between 1500 and 1100 cm −1 were due to the C–H stretching and O–H bending vibrations of phenols (Patle et al., 2020). The bands allocated at 1072 and 1015 cm −1 were due to the C–O stretching vibration of phenols (Kustrin et al., 2021). The C = C bond of the phenolic compounds due to the aromatic rings was seen at 921 cm −1 (Istúriz‐Zapata et al., 2022).…”
Section: Resultsmentioning
confidence: 99%